Black Popular Culture Lecture Series brings actor Delroy Lindo to Fresno State - Schock, Kathleen::::::::: (2013)
Stage and screen actor Delroy Lindo, known best for his roles in films like 'Malcolm X,' 'Get Shorty' and 'Gone in 60 Seconds,' comes to Fresno State as the inaugural speaker in the Black Popular Culture Lecture Series.